Efficacy and safety evaluations of anlotinib in patients with advanced non-small cell lung cancer treated with bevacizumab - Jiang, Fenge; Li, Junxia; Kong, Xiangshuo; Sun, Ping; Qu, Huajun (Frontiers in Pharmacology, 2022)
Objective:The purpose of this study was to evaluate the efficacy and safety of anlotinib in patients with advanced NSCLC who had previously received bevacizumab. Methods: Histopathological or cytological diagnostic as advanced NSCLC patients whose disease progressed after at least one type of systemic therapy and who had previously received bevacizumab treatment. The patients were on three-week administration cycles including two weeks on-treatment (12 mg anlotinib oral route once a day) and one week off-treatment. The primary end point of the trial was overall survival (OS). The secondary end points were progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR) and safety. Results: As of the data collection deadline (March 31, 2021), 30 patients were enrolled the study and received anlotinib treatment. All patients were included in the data set except one withdraw the consent after the treatment starts. The median follow-up period was 12.1 months (range, 3.6-25.0 months) and 29 patients were included in the evaluation of the treatment. Of the 29 patients, no CR cases occurred. In total, 3 patients (10.2%) showed a PR, 21(72.4%) had SD, and 5 patients (17.2%) had PD. The ORR was 10.2% (3 of 29 patients), and the DCR was 82.7% (24 of 29 patients). The median PFS was 5.6 months (95% CI, 5.0 to 6.1 months; Figure 2). The median OS was 10.6 months (95% CI, 9.4 to 11.8 months; Figure 3).The overall tolerance of the anlotinib treatment was very well among the enrolled patients. No treatment-related grade four or five toxicities were observed. Of the 29 patients, one patient’s anlotinib administration was reduced to 8mg/day due to hypertension and headache. Most adverse events (AEs) were grade one or two, the most common AEs were fatigue (51.7%), hypertension (41.3%), hand-foot syndrome (38.0%), anorexia(34.5%), and hypertriglyceridemia(34.5%). Conclusions: Anlotinib demonstrated favorable activity and manageable toxicity in NSCLC with patients treated with bevacizumab previously.